MORPHOLOGICAL FEATURES OF THE YELLOW BODY IN WOMEN (Modern education and development, 2024)
The corpus luteum is an important structure of the ovarian membrane after ovulation, which is formed from a ruptured follicle and produces sex hormones – progesterone and a small amount of estrogen. These hormones prepare the uterine lining for implantation and help maintain pregnancy. The corpus luteum consists of granulose lutein and theca lutein cells, each of which performs a specific function in the hormone production process. This process is supported by blood vessels and connective tissue.If fertilization does not occur, the corpus luteum regresses and turns into a white body (white body). Conversely, when fertilization occurs, the corpus luteum continues to produce progesterone in the early stages of pregnancy. The formation, structure and functions of the corpus luteum play an important role in managing a woman's reproductive cycle, as well as in creating the hormonal environment necessary for pregnancy.